2016
DOI: 10.1183/23120541.00034-2015
|View full text |Cite
|
Sign up to set email alerts
|

Understanding variation in length of hospital stay for COPD exacerbation: European COPD audit

Abstract: Chronic obstructive pulmonary disease (COPD) care across Europe has high heterogeneity with respect to cost and the services available. Variations in length of stay (LOS) may be attributed to patient characteristics, resource and organisational characteristics, and/or the so-called hospital cluster effect.The European COPD Audit in 13 countries included data from 16 018 hospitalised patients. The recorded variables included information on patient and disease characteristics, and resources available. Variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 43 publications
4
44
1
Order By: Relevance
“…It was noticed a high predominance of male smokers among COPD inpatients (n=112/162; 69.1%) versus females (n=12/33; 36.3%), for odd ratio (OR) of 2.05 (0.84-4.96) and risk ratio (RR) of 1.32 (0.88-1.98), without significant differences of distribution by gender (chi 2 =2.6, p= 0.106). Professional exposure to particles and dust was incriminated in 75.9% of cases (n=123/162), a high incidence consistent with other studies [16]. The clinical implications of respiratory failure among COPD inpatients varied from aggravated exertional dyspnea, increase in volume and purulence of sputum, to resting dyspnea, orthopnea, cyanosis, weakness, paradoxical breathing as a sign of muscle fatigue described in 170 patients (87.17%).…”
Section: Resultssupporting
confidence: 80%
“…It was noticed a high predominance of male smokers among COPD inpatients (n=112/162; 69.1%) versus females (n=12/33; 36.3%), for odd ratio (OR) of 2.05 (0.84-4.96) and risk ratio (RR) of 1.32 (0.88-1.98), without significant differences of distribution by gender (chi 2 =2.6, p= 0.106). Professional exposure to particles and dust was incriminated in 75.9% of cases (n=123/162), a high incidence consistent with other studies [16]. The clinical implications of respiratory failure among COPD inpatients varied from aggravated exertional dyspnea, increase in volume and purulence of sputum, to resting dyspnea, orthopnea, cyanosis, weakness, paradoxical breathing as a sign of muscle fatigue described in 170 patients (87.17%).…”
Section: Resultssupporting
confidence: 80%
“…Notably, duration of hospitalisation in the COPD control group is consistent with that quoted in a large, contemporaneous UK study. 25 The reduction in length of stay for patients with exacerbation of airways disease was in the order of 1 day, which would equate to around 200 000 bed days saved per year across the NHS with an associated cost saving of around £80 million per year (a formal health economic analysis of our trial will be published separately). 26 Routine POCT for respiratory viruses was also associated with an increased rate of detection of influenza cases and an improvement in antiviral use.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in 13 European countries with 16,018 patients diagnosed with COPD found that the main factors associated with prolonged length of stay were related to the severity or exacerbation of the disease. With effective and timely health care, these individuals should not reach the hospital unit so debilitated 24 .…”
Section: Discussionmentioning
confidence: 99%